No depression for my old heart, before and after the event - de Lima, Michele; Escobar Guzman, Luis Fernando; Escobar Guzman, Cristian Andrés; Lanz-Luces, José Ramon; Lanz-Souquett, José Daniel (Gaceta Médica de Caracas, 2022)
Background: Depression and cardiovascular diseases (CVD) are highly prevalent in the elderly. Depression could be a CVD risk factor as well as an ailment sequela. Objective: To review diagnostical, pathophysiological, and therapeutic factors involved in depression-cardiovascular diseases. Methods: The research was carried out using the keywords of a 10-years range of published studies in Portuguese, English, and Spanish from Scielo and PubMed databases. Inclusion criteria: In vitro studies, cohort studies, case-control, and clinical trials. Studies out of time range, mean age <60 years, other psychiatric diseases were excluded.